Dynamic Compensation of a Fluxgate Magnetometer Based on a Hybrid Optimizing Algorithm - Zhuo Chen; Zhenxiong Wang; Qi Zhang; Zhongyan Liu; Mengchun Pan; Dixiang Chen; Yujing Xu (Applied Sciences, 2023)
Under dynamic conditions, when the measured magnetic field is projected onto the sensitive axis of the fluxgate magnetometer, it will show strong dynamic characteristics, resulting in errors or delayed interpretation of the measured physical process. Considering the dynamic characteristics of the three-axis fluxgate magnetometer, this paper proposes a series dynamic compensator based on system identification to carry out system identification and modeling of the dynamic characteristics of the three-axis fluxgate magnetometer and proposes a system parameter calculating method based on hybrid optimization of the genetic algorithm and the simulated annealing algorithm (GA-SA). With these methods, not only can the parameter optimization process effectively avoid falling into the local optimal, but they can also greatly improve the search efficiency and shorten the time of solving the optimal solution. Thus, the full-space search ability of the algorithm is improved, and the accuracy of the dynamic magnetic measurements is improved to the maximum extent. The simulation results of the step signal show that the response time is reduced to 18.22% of the pre-compensation time. The standard signal test results of the step signal and sinusoidal signal, respectively, show that the response time of the step signal is reduced to 5.5% and, in the 0.01–10 Hz frequency band, the maximum attenuation decreases from 0.24% to 0.10%, and the phase difference is less than −0.5°. Moreover, the experimental results of the geomagnetic dynamic measurements show that the dynamic compensated data are mostly close to the real geomagnetic field values. In addition, the standard deviation errors are reduced from 95.30/277.35/108.51 nT to 3.41/2.36/2.75 nT in three geomagnetic vector components. The results of this work show the ability of dynamic measurement accuracy improvement of fluxgate magnetometers and are useful for geomagnetic dynamic measurement and related applications.